1998
DOI: 10.2466/pr0.83.5.19-64
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Biorhythm Theory

Abstract: Biorhythm theory which became popular with the general public in the late 1960s held that three different biorhythm cycles influenced three different general aspects of human behavior. There was a 23-day cycle which influenced physical aspects of behavior. A 28-day cycle influenced emotions and a 33-day cycle influenced intellectual functions. Further, according to the theory, these three cycles started at birth and progressed, sinusoidally, throughout life varying not a bit with environmental or physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Smoking tends to have a negative impact on PA performance, and this may influence active young adults to refrain from smoking. However, motivations behind smoking behaviors may vary among young adults; for example, it is interesting to note that previous research has found that 56% of young adult females felt smoking helped them control their weight [30]. Thus some young adults may be choosing to smoke in an effort to control their weight, rather than engaging in healthy weight control behaviors, such as PA. Additional research is needed to examine the use, adoption and role of weight control behaviors in this population, particularly in relation to other risk behaviors and among lower SES young adult populations where limited research is available.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking tends to have a negative impact on PA performance, and this may influence active young adults to refrain from smoking. However, motivations behind smoking behaviors may vary among young adults; for example, it is interesting to note that previous research has found that 56% of young adult females felt smoking helped them control their weight [30]. Thus some young adults may be choosing to smoke in an effort to control their weight, rather than engaging in healthy weight control behaviors, such as PA. Additional research is needed to examine the use, adoption and role of weight control behaviors in this population, particularly in relation to other risk behaviors and among lower SES young adult populations where limited research is available.…”
Section: Discussionmentioning
confidence: 99%
“…Lacking any direct means of taking account of plausibility, the NHST paradigm is notoriously capable of lending support to patently spurious claims (e.g., Hines 1998;Austin et al 2006;Bennett, Miller, and Wolford 2009). While often blamed on practices such as data-dredging, failure to take account of plausibility is more pernicious as it can undermine entire areas of research (e.g., Bracken 2009; Ioannidis 2013).…”
Section: The Inability Of P-values To Incorporate Plausibilitymentioning
confidence: 99%
“…Biorhythms, the lunar lunacy effect (Hines, 1998;I. W. Kelly, Rotton, & Culver, 1985;Raison, Klein, & Steckler, 1999; Class 8…”
Section: Courses In the Science And Pseudoscience Of Psychology: A Momentioning
confidence: 99%